2019
DOI: 10.1042/bst20180165
|View full text |Cite
|
Sign up to set email alerts
|

Engineering quorum quenching enzymes: progress and perspectives

Abstract: Quorum sensing is a key contributor to the virulence of many important plant, animal and human pathogens. The disruption of this signalling—a process referred to as ‘quorum quenching’—is a promising new approach for controlling microbial pathogens. In this mini-review, we have focused on efforts to engineer enzymes that disrupt quorum sensing by inactivating acyl-homoserine lactone signalling molecules. We review different approaches for protein engineering and provide examples of how these engineering approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 61 publications
(63 reference statements)
0
33
0
Order By: Relevance
“…QS inhibitors fall into two categories: QQ enzymes and certain chemicals extracted from natural resources or obtained by chemical synthesis [ 46 , 47 , 48 , 49 ]. In isolating QQ enzymes from bacteria, it has been confirmed that there are a variety of strains presenting QS signal inactivation capabilities in different microbial genera [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QS inhibitors fall into two categories: QQ enzymes and certain chemicals extracted from natural resources or obtained by chemical synthesis [ 46 , 47 , 48 , 49 ]. In isolating QQ enzymes from bacteria, it has been confirmed that there are a variety of strains presenting QS signal inactivation capabilities in different microbial genera [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that resistance is less likely to develop, because QQ strains impart less selective pressures. However, resistance attributes to QS inhibitors have already been discovered in laboratory and clinical settings [ 25 , 52 ]. Therefore, it is a considerable and notable phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Antivirulence therapies. The 33 antivirulence projects that we identified are pursuing a wide range of strategies, including inhibition of quorum sensing, biofilm formation, adhesion, diverse regulators and persisters [67][68][69][70][71] . Antivirulence drugs need to be combined with a direct-acting antibacterial therapeutic and are designed as adjunctive therapies.…”
Section: Compassionate Usementioning
confidence: 99%
“…the use of a quorum-quenching enzyme to disrupt bacterial communication, leading to the inhibition of biofilm formation. 17) With the number of phages already sequenced, and the techniques available to improve enzyme function [18][19][20] and phage manipulation, these approaches could constitute a useful weapon to incorporate into future strategies.…”
Section: Engineering Host Specificitiesmentioning
confidence: 99%